Patient safety and public health concerns: poor dissolution rate of pioglitazone tablets obtained from China, Myanmar and internet sites - Mohammad Sofiqur Rahman; Naoko Yoshida; Hirohito Tsuboi; Erina Maeda; Andrea Vanessa Velasco Ibarra; Theingi Zin; Yoshio Akimoto; Tsuyoshi Tanimoto; Kazuko Kimura (BMC, 2021)
Abstract Background Poor quality medicines have serious implications for public health. The aim of this study was to explore the quality of the antidiabetic pioglitazone, using samples collected in China and Myanmar, and samples purchased online. Methods In this cross-sectional study, we examined samples (n = 163) collected from hospitals in Shanghai, China in 2012 (n = 44), products purchased via the internet and imported into Japan in 2013 (n = 59), and samples purchased in shops in Yangon, Myanmar in 2015 (n = 60). Collected samples were subjected to visual inspection, authenticity investigation and quality testing (potency, content uniformity and dissolution test) by high-performance liquid chromatography. Samples were rated as compliant or non-compliant based on the relevant pharmacopoeial acceptance criteria. Results Visual inspection of all samples revealed compliant products. However, responses from manufacturers during authenticity investigation were poor. Among the n = 44 samples from China, one was non-compliant in the potency test. Among the n = 59 samples personally imported into Japan, 38% of generic samples were found to be non-compliant. In Myanmar, 13.3% of samples were non-compliant. Non-compliant samples predominantly failed in the dissolution test. All non-compliant samples were generic. Conclusions Despite the apparent satisfactory outcome on the samples from China, pioglitazone samples collected in Myanmar and purchased online for personal import into Japan included many substandard products, which failed quality assessment predominantly because of poor dissolution. Internet providers did not comply with Japanese regulations in various respects.